Implementasi Face Recognition Pada Aplikasi Absensi Berbasis Android Menggunakan Algoritma Haversine - Siddiq Assegaf, Djafar; Azhar, Ryfial; Pusadan, Yazdi; Anggun Pratama, Septiano; AR. Lamasitudju, Charunnisa (The Indonesian Journal of Computer Science, 2024)
Android-Based Attendance Application, Face Recognation, Haversine Algorithm, Management System. The attendance system is a method for managing employee presence, which contributes to productivity and accountability. This study aims to implement an Android-based attendance application that utilizes face recognition technology and the Haversine algorithm to enhance the accuracy and efficiency of the attendance process. Face recognition is applied to automatically verify user identity and reduce the risk of fraud in the attendance process. The system integrates the Haversine algorithm and face recognition, where the Haversine algorithm is used to calculate the distance between the employee's location and the office, ensuring that attendance can only be recorded within a predetermined radius. The results indicate that this system is effective in determining employee attendance status with high accuracy, recording employees within a radius of ≤ 30 meters as present. Additionally, the use of face recognition technology accelerates the attendance process and improves accountability. These findings open opportunities for further research in integrating technology into human resource management and are expected to enhance transparency and efficiency in managing employee attendance across various sectors.